Writing a good anticipatory care plan for a child with severe disability. Issue 10 (October 2019) - Haynes, Sarah; Dorsett, Caroline; Wolff, Toni
Abstract: There are increasing numbers of children with severe disability and life limiting conditions living longer in the community. In order for them to have high quality end of life care and choice of place of death there need to be discussions with the child and family about how the child may deteriorate and the pros and cons of the different possible interventions taking into account the priorities and views of the family and the child themselves. Families and professionals are reluctant to talk about the death of a child and there is always uncertainty. Parallel planning for best and worst case scenarios can be helpful and offering families a useful medical emergency care plan for their child is a positive way to start to plan for deterioration and life threatening events. The emergency care plan can include the resuscitation plan and the child and family priorities of care and leads on to further discussions about choices in end of life care including place of death and funeral plans.